Synthesis and Characterization of Oligothiophene–Porphyrin-Based Molecules That Can Be Utilized for Optical Assignment of Aggregated Amyloid-β Morphotypes - Arja, Katriann; Elgland, Mathias; Nilsson, K. Peter R. (Frontiers in Chemistry, 2018)
Molecular tools for fluorescent imaging of protein aggregates are essential for understanding the significance of these pathological hallmarks in proteopathic neurodegenerative diseases, such as Alzheimer´s disease. Here, we report the synthesis of a series of oligothiophene porphyrin hybrids, OTPHs, and the evaluation of these dyes for fluorescent imaging of beta-amyloid aggregates in tissue sections from a transgenic mouse model with Alzheimer's disease pathology. The OTPHs proved to be successful for spectral and lifetime imaging assessment of protein deposits and our findings confirm that the enhanced spectral range and distinct lifetime diversity of these novel tools allow a more precise assessment of heterogeneous amyloid morphology compared with the corresponding oligothiophene dye. In addition, the chemical identity of the porphyrin moiety, as well as the spacing between the two optical active moieties, influenced the OTPHs performance for fluorescent assignment of the protein deposits. We foresee that our findings will aid in the chemical design of dyes that can be utilized as optical tools for studying the polymorphic nature of protein aggregates associated with proteopathic neurodegenerative diseases.